7p+2p+9p-2=

Simple and best practice solution for 7p+2p+9p-2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7p+2p+9p-2= equation:


Simplifying
7p + 2p + 9p + -2 = 0

Reorder the terms:
-2 + 7p + 2p + 9p = 0

Combine like terms: 7p + 2p = 9p
-2 + 9p + 9p = 0

Combine like terms: 9p + 9p = 18p
-2 + 18p = 0

Solving
-2 + 18p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 18p = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 18p = 0 + 2
18p = 0 + 2

Combine like terms: 0 + 2 = 2
18p = 2

Divide each side by '18'.
p = 0.1111111111

Simplifying
p = 0.1111111111

See similar equations:

| j^2k^2= | | 4v^2+4=7 | | b^2-7b+17=7 | | xa+3b=2f | | 2x-4=4(x+4) | | y+5=5y | | f(x)=(x^2+1)(x^3-x) | | 25+30x=2 | | (j^2k^3)(jk^2)= | | b^2-7b=17 | | 6x=109 | | -4x^2+11x-20=0 | | -6a+7=-2a+-3 | | -1/2+(-2/3)= | | 3x+108=9x-6 | | 3x+108=9x+6 | | 4x+15=87 | | 6(2x-1)-9=12x-15 | | 4-3x=8+5x | | 49=2v+15 | | 8/4.5=x | | 5x^3+16x^2+12x=0 | | 2x-6=2(x-1) | | 3m=mp+7 | | x-5/8=1/2 | | (2x-7)-(7-z)-2z=0 | | (15x-5)=90-4x | | 9x=3x+5 | | -2x-2(1+8x)=-4(x+4) | | 3w-16=17 | | 36=-39 | | 36=-36 |

Equations solver categories